Efficiency of the Sucrose-Based Solution and UW Solution for Hypothermic Storage of Human Mesenchymal Stromal Cells in Suspension or Within Alginate Microspheres - Tarusin, Dmitriy N.; Petrenko, Yuriy A.; Semenchenko, Olga A.; Mutsenko, Vitaliy V.; Zaikov, Vedeney S.; Petrenko, Aleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2015)
The effect of hypothermic storage (HS) on viability and functional activity of human mesenchymal stromal cells (MSCs) in suspension and within alginate microspheres (AMSs) was studied. Cells were stored in sealed cryovials at 4°C in culture medium (CM), sucrose-based solution (SBS) and that of the University of Wisconsin (UW). After 3 and 7 days of storage the viability, metabolic activity and morphology of MSCs were assessed by MTT-assay, Alamar Blue test, adhesive activity, morphology and ability of multilineage differentiation at monolayer culture conditions. Hypothermic storage of MSCs suspension in CM for 3 days was established to result in a 3–4-fold decrease in their viability and adhesive ability. The encapsulation into AMSs partially prevented cell death. Hypothermic storage for 7 days caused death of almost all MSCs both in suspension and AMSs. The substitution of CM for UW and SBS preservation solutions maintained the MSCs viability and metabolic activity following HS within 3 days both in suspension and within AMSs. After 7 days of HS in UW and SBS solutions the MSCs in suspensions and within AMSs preserved their viability on the level of 60–80%, adhesive properties, metabolic activity, as well as the ability for induced adipogenic and osteogenic differentiation. The use of UW and SBS preservation solutions enabled to prolong the hypothermic storage terms for MSCs. Probl Cryobiol Cryomed 2015; 25(4):329-339.